Apparent Henry's law constants of furan in different n-alkanes and alcohols at temperatures from 293 to 323 K. Issue 1 (February 2017) - Hajiw, Martha; Valtz, Alain; Ahmar, Elise El; Coquelet, Christophe
Abstract: Green chemical compounds with high added value can be obtained after pyrolysis of lignocellulosic biomass. This biomass is playing a major role in the chemical sectors as a substitution material. This study is focused on one of these compounds, furan. High selectivity of a solvent is the most important criteria for an optimised extraction. In other words, for the selected solvent, activity coefficients of the compounds to be separated must be different. Therefore, experimental activity coefficients of compounds of interest in different solvents are necessary. In this paper, apparent Henry's law constants of furan in different n -alkane and alcohol solvents have been measured at temperatures from 293 to 323 K using the inert gas stripping method to analyse their potential for furan extraction. Besides, if the value of limiting activity coefficient is close to one, it is an indicator of its suitability for the compound extraction.